Avaliação histomorfométrica de alvéolos dentários humanos pós-extração tratados com fibrina autóloga, fosfato de cálcio bifásico ou sua associação - Ponte, José Sandro (2020)
The maintenance of the alveolar bone ridge is prerogative for the success of implant therapy, following this aspect the use of biomaterials (grafts and membranes) in guided bone regeneration techniques are indicated as a recognized standard for bone reconstructions. Biomaterials have evolved over the years, in this aspect, a platelet concentrate, platelet-rich fibrin (PRF) emerges as an autologous biomaterial, with healing and tissue repair power. Its application alone or in synergism with another biomaterial could generate promising results in alveolar repair. The aim of this work was to histomorphometrically analyze human dental alveoli after extraction treated with autologous fibrin, biphasic calcium phosphate or an association of both. Sixteen surgical beds were selected in fifteen voluntary, normosystemic patients, between twenty and forty-five years old, recruited at the dental clinic of UFC Sobral, with indication of post-extraction graft of upper premolars for maintenance of the alveolar ridge and subsequent implantation. All underwent radiographic and tomographic exams to diagnose bone condition before graft surgery and before implantation. The surgical procedure was divided into two stages, with an interval of eight months, the first for removing the dental element and grafting the biomaterial, the second aiming at bone collection and implant insertion. After eight months, five participants did not continue with the survey. In the second surgical step, we obtained eleven samples from ten patients, which were divided into three groups. Each group of patients received a type of treatment by dental socket: filling with autologous fibrin in the form of a plug covered by a fibrin membrane (G1), fibrin associated with an alloplastic graft based on hydroxyapatite and beta tricalcium phosphate covered by a collagen membrane (G2) or alloplastic graft based on beta tricalcium phosphate covered by collagen membrane (control). The histomorphometric evaluation of each sample was based on three microtomies and ten histological fields per microtomy, analyzing the mean and standard deviation of newly formed bone, connective tissue, remaining biomaterial and other structures. Parametric data were analyzed by ANOVA and Tukey's post-tests and statistical significance of 5% (p <0.05) and followed normality assessment with the Jarque-Bera (JB) test. There was a higher mean of neoformed bone in G1 (68.83% 4.95) compared to G2 (35.69% 7.86) and control (16.28% 13.90). The control had a greater presence of connective tissue (61.56% 11.85), followed by G2 (32.67% 13.69) and G1 (13.95% 3.48). There was a greater presence of biomaterial in G2 (15.75% 11.63), but without statistical difference for the control group (8.43% 3.10). The other structures parameter followed without statistical differences, G1 (17.21% 5.53), G2 (15.88% 7.06) and control (13.73% 4.78). The good bone regeneration pattern obtained with the use of isolated fibrin suggests the efficacy and effectiveness of this therapeutic modality, stimulating the clinical use of this platelet concentrate in the dental office.